The Development of Early Childhood Motor through Human Resource Empowerment of PAUD Teacher Using Educational Game Tools in Maos Lor, Cilacap District, Central Java Province - Dodi Satriawan (Jurnal Pengabdian Barelang, 2019)
Improving education and training of teacher as a focus on reformation of educational system which is a goal that must be achieved in EFA (Education for All). As a tangible manifestation of the mandate through efforts to improve the quality of education and development of competency based on educational game tools or APE. PAUD teachers should also have the ability to design, create, utilize, maintain, and self-assess the tools for early childhood games because well-developed game tools will be more interesting than tools that were not developed first. This community service program activity is needed because the education level of PAUD teachers varies. Based on the results of the identification of the target audience, most PAUD teachers do not meet the academic qualifications and competencies properly. The ability to read, write, count, think actively and critically and the low implementation of learning models in the form of quality and fun educational teaching aids in PAUD institutions is very necessary. The expected output of this activity is the increasing, competency and quality of PAUD teachers towards educational game-based media learning programs (APE) and increasing the creativity of PAUD students by implementing APE-based learning media programs.